2019
DOI: 10.1038/s41591-019-0404-8
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of cancer cell line metabolism

Abstract: Despite considerable efforts to identify cancer metabolic alterations that might unveil druggable vulnerabilities, systematic characterizations of metabolism as it relates to functional genomic features and associated dependencies remain uncommon. To further understand the metabolic diversity in cancer, we profiled 225 metabolites in 928 cell lines from more than 20 cancer types in the Cancer Cell Line Encyclopedia (CCLE) using liquid chromatography-mass spectrometry (LC-MS). This resource enables unbiased ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
400
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 427 publications
(431 citation statements)
references
References 30 publications
29
400
2
Order By: Relevance
“…ASNase could break down both asparagine and glutamine, even though its glutaminase activity was not required for ASNS‐negative cancer cells (Chan et al , ). Moreover, ASNase was found effective in treating solid tumors with intrinsic loss of ASNS (Li et al , ). We observed that in cell culture conditions, both asparagine and glutamine were robustly depleted by ASNase (Fig G).…”
Section: Discussionmentioning
confidence: 99%
“…ASNase could break down both asparagine and glutamine, even though its glutaminase activity was not required for ASNS‐negative cancer cells (Chan et al , ). Moreover, ASNase was found effective in treating solid tumors with intrinsic loss of ASNS (Li et al , ). We observed that in cell culture conditions, both asparagine and glutamine were robustly depleted by ASNase (Fig G).…”
Section: Discussionmentioning
confidence: 99%
“…As such, the global lipid landscape of cancer cell lines greatly differs from noncancerous cells . Indeed, recent evidence also shows that substantial lipid diversity exists within distinct types of cancer cells …”
Section: Lipid Metabolism and Leukaemiamentioning
confidence: 99%
“…91 Indeed, recent evidence also shows that substantial lipid diversity exists within distinct types of cancer cells. 92 Sphingolipid synthesis is a tightly regulated process that is thought to be self-regulated. Importantly, enzymes involved in sphingolipid metabolism have been identified as targets for the Runx family of genes with glucosylceramide and ganglioside synthesis being upregulated and S1P catabolism downregulated upon Runx activation.…”
Section: Lipid Metabolism and Leukaemiamentioning
confidence: 99%
“…The inherent plasticity of cellular metabolism and the high degree of metabolic heterogeneity in TNBCs pose great challenges for metabolism targeting therapy 21 . Recent work suggests that heterogeneous metabolic dependencies within cancer cells underline the differential therapeutic vulnerabilities 22 . Therefore, in order for GLUT1 inhibition to be a successful strategy for TNBC therapy, the precise contexts in which this metabolic pathway is essential needs to be identified.…”
Section: Introductionmentioning
confidence: 99%